PENDAMPINGAN PEMBUATAN DESAIN INTERIOR TEMA KOLONIAL BAGI UKM KANTIN MESRAN KAWASAN TITIK NOL - Yashinta Irma Pratami Hematang; Sari Octavia (Musamus University, 2019)
Partners proposed in this community service program is SME (Micro Small Business) Kantin Mesran Kawasan Titik Nol. The canteen is located on the colonial buildings, the former gas stations in the Dutch Period in Merauke. According to the BPS (2014), Kantin Mesran is one of historic sites. Although the owner realizes the compatibility of the colonial theme but it has not been applied maximally to the canteen. This is due to many factors such as the absence of a background of design knowledge owned by the owner of the canteen. Because the design is assisted by a dedicated team, it can cut maintenance and redesign costs by teams with appropriate areas of expertise, thus becoming a cultural heritage conservation effort. Partners are accompanied by a team of dedication to be able to understand the basic concepts of colonial design so that the activities of maintenance and renovation of old buildings can run well and the principle of preservation goes well in the future. Partners are also invited together in the preparation of design exploration. The results of mentoring are: partner's understanding of colonial interior design, historic building documentation of Merauke, and the results of the design during the mentoring activities.